Evaluation of the Kuznets Hypothesis for Colombia 1977-2005 - Alonso Cifuentes, Julio César; González Terán, Ángela María (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Inequality in a country can have serious consequences in the economic development and that is why it is important the study of the causes of its variations. Therefore, this document aims to explain how is affected the income inequality by changes in economic growth, population and nominal exchange rate. Following the Kuznets curve hypothesis (1955), a bad indicator of inequality in the short term is necessary to achieve better equality in the long term as an effect of the economic growth. The study is done for Colombia, between 1977 and 2005, with quarterly data. Our results show that the relation between economic growth and income distribution can be explained by the Kuznetshypothesis.